Exploring age-related changes in gut bacterial community composition of yak: insights from different age groups - Tariq Shah; Xusheng Guo; Gulraiz Ahmad; Muhammad Ishaq; Ahmad Ud Din; Sadia Sardar; Luming Ding (BMC Microbiology)
Abstract Background The Qinghai-Tibetan Plateau (QTP) offers one of the most extreme environments for yaks (Bos grunniens). The yak is an indigenous species, and the wild yak was domesticated on the QTP. The gut microbiota plays a vital role in health and animal performance. However, little is known about the progression of gut microbes in different age developmental stages of domesticated yaks. Method We used the 16 S rRNA gene sequencing method to explore the progression of the fecal bacterial microbiota of 18 different confined domestic yaks at two developmental stages: 3 to 5 years (GT35) and 6 to 8 years (GT68). Results We found significant differences in gut bacterial communities between the two age groups. The diversity of the gut bacterial community was significantly lower in the GT35 group, which reached stability with age. Bacteroidetes and Firmicutes were the two dominant phyla between the two age groups. Phylum Firmicutes was significantly higher in the GT68 group, and Proteobacteria, Spirochaetes, Tenericutes, and Actinobacteria were highly abundant in the GT35 age group. Genera Bacteroides, Alloprevotella, and Anaerovibrio were abundant in the GT35 group. The short-chain fatty acid (SCFA) producing bacteria Rikenellaceae showed higher abundance in GT35. The core bacterial microbiota of the GT68 age group was dominated by Ruminococcaceae and Rikenellaceae. The gut bacterial community has a great variation between the groups. Based on the exploration of dynamic changes in the gut bacterial community at different ages, our results illustrate that yaks undergo a process of reaching stability and maturity as they age.